IMPLEMENTASI DESIGN UI/UX APLIKASI TOKO EKSHAN STORE SKINCARE UNTUK OPTIMASI PENJUALAN PRODUK - Ardhani, Rahmad; Munir, Muhammad Misbahul; Setiyaningrum, Bekti (Journal of Social Computer and Religiosity (SCORE), 2025)
The growth of the skincare industry in Indonesia has experienced rapid development along with increasing public awareness of skincare. The high level of market competition motivates business actors to optimize their sales activities, including through the use of digital technology. This study aims to apply User Interface and User Experience to the Ekshan Store Skincare application to optimize the effectiveness of sales activities. The research method implemented includes a User-Centered Design (UCD) approach with a process of analyzing user needs, designing prototypes, testing usability (usability test), and evaluating implementation results. Data collection was carried out using interviews, questionnaires, and observations of potential application usage. This study involved 4 potential users of the Ekshan Store Skincare with an age range of 20–35 years. Respondents' responses mostly work as students, private employees, freelancers, housewives, and content creators. Their average frequency of skincare shopping is around one to four times a month. The research findings show that the implementation of responsive, consistent, and user-friendly UI/UX design has a positive effect on user comfort, improves engagement, and encourages sales conversions. This progress indicates that appropriate UI/UX design can be an effective option for skincare businesses competing in the digital realm.